DESIGN OF A VIBRATING MACHINE MODULE FOR POLLUTION CLEANING AND A GENERAL METHOD FOR CALCULATING ITS ELEMENTS - HORDIEIEV, Anatolyi; STARIY, Andriy; URBANIUK, Evgeniy; HORDIEIEV, Alexei (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The quality and reliability of repaired machines depend significantly on the perfection of the technological processes of disassembly, cleaning, surface preparation and assembly. The analysis of methods and modern designs of equipment and machines for cleaning and washing pollution showed the possibilities, advantages and disadvantages of various methods and designs of equipment. The main interest for the practice of creating vibrating machines for cleaning and washing parts contamination in small-batch and single-type production when repairing machines is to establish the type of dependencies between the main technological parameters, such as the dynamic pressure of the working environment, the size of the working bodies, their speed, the angle of attack, design parameters and modes of operation of the drive of vibrating machines. The design of a vibrating machine for cleaning contamination with a stream of solid particles and washing parts during equipment repair is proposed, which consists of two modules: a cleaning module with a pulsating submerged jet with solid particles and a module for washing contamination with a pulsating submerged jet of washing liquid. Experimental studies were conducted to measure the maximum pressure of a pulsating jet with a non-return valve installed, depending on the change in the frequency of oscillations of the drive and the change in the diameter of the nozzle. The results of experimental studies of changes in the pressure of a pulsating submerged jet depending on the frequency of oscillations of the drive are presented, which showed a two-fold increase in the maximum pressure of a pulsating submerged jet when using a non-return valve that connects the cleaning bath with the pulsation chamber. In order to reduce the occurrence of a significant number of cavitation bubbles in the pulsation chamber for the non-return valve, it is important to calculate the maximum total area of the holes and their number, based on the volumetric flow of liquid through it during the oscillation period. The determined valve operation time is 0.014s. says that its performance is ensured at frequencies from 0 to 70 Hz of vibrations of the vibration drive. The methodology and example of calculation of the non-return valve of the module of the vibrating machine for cleaning pollution by the flow of a pulsating jet of liquid with solid particles are presented.
Keywords: vibration machine; pulsating immersed liquid jet with solid particles; maximum liquid pressure; design method